AC-driven atmospheric pressure glow discharge co-improves conversion and energy efficiency of CO2 splitting. (April 2023) - Meng, Guodong; Xia, Linghan; Cheng, Yonghong; Yin, Zongyou
Abstract: Gap distance and discharge power have great influence on the morphology and characteristics of glow plasma. Unfortunately, there is few research on the influence law and mechanism of these factors for CO2 splitting by glow plasma. In this study, an AC-driven atmospheric pressure glow discharge (APGD) plasma reactor was developed for CO2 splitting. Through the rational design on the plasma reactor accompanied by numerical simulation and systematic experimentation, the unique influence laws and mechanisms on CO2 splitting behavior are unveiled. Several key parameters, such as gap distance, discharge power and gas flow rate, are found able to play synergistic roles in tailoring plasma reactor to co-improve the conversion and energy efficiency. At an optimized gap distance, sufficient electron collisions along the main channel results in the largest active plasma volume, leading to the optimal CO2 splitting performance. The conversion and energy efficiency could also be co-improved by synchronously increasing the discharge power and gas flow rate at a given specific energy input (SEI) value, which exhibits an opposite feature of dielectric barrier discharge (DBD) plasma, because larger plasma volume increases the probability of collision dissociation reaction and lower gas temperature decreases the rate of recombination reaction. The AC-driven APGD reactor can achieve maximum conversion of 11.96% and maximum energy efficiency of 41.51% which superior to the results of most atmospheric pressure plasmas. This work gains insights into the behaviors of AC-driven APGD plasma in CO2 splitting and potentially opens an avenue to develop plasma technology for sustainable CO2 utilization. Graphical Abstract: ga1 Highlights: A custom-designed AC-driven APGD reactor for CO2 splitting is developed. Unique influence laws and mechanisms on CO2 splitting behavior are unveiled. The conversion and energy efficiency could be co-improved by synergistic effects. The maximum conversion of 11.96% and energy efficiency of 41.51% are realized.